Cephalometric analysis for accurately determining the vertical dimension: a case report - Wahipa Wiro; Ike D. Habar (Journal of Dentomaxillofacial Science, 2017)
Objective : Determination of the vertical dimension of occlusion (DVO) tends to changes throughout the human life. The vertical dimension is determined by the interocclusal point of the upper and lower teeth contact so the application is limited when the natural teeth was missing. As the result, many functional and aesthetic changes are occurred in the whole orofacial region and stomatognathic system. DVO is one of the difficult stages in prosthodontic treatment. Most of the techniques to determine DVO in edentulous patients are based on the soft tissue references, which can cause the different measurements. Cephalometric analysis allows the evaluation of bone growth changes and can be used as a diagnostic tool in prosthodontics to evaluate the results of prosthodontic rehabilitation.Methods : The purpose of this case report was to find out the results of the vertical dimension of occlusion measurements in maxillomandibular relation by using cephalometric photo in patients who have been long lost their teeth and have never been using denture.Results : A 50 year old female patient, partially edentulous on the upper and lower jaw with the remaining teeth were 12 (residual root), 11,21,23,33 and 43. The remaining teeth were endodontically treated prior the complete denture procedure. Cephalometric photo was done in patients after making bite rim, upper and lower bite rim were given metal marker, the image was traced, then measured between metal to get the vertical dimension of occlusion.Conclusion : The measurement results of the vertical dimension of occlusion by using cephalometric photo on making full denture were more accurate, so it could improve and restore the masticatory function, aesthetic function and phonetics.